Hubungan Kunjungan Trimester 1 dengan Screening Anemia pada Ibu Hamil di Era Peradaban Baru - Yuni Khoirul Waroh (Jurnal Kebidanan Harapan Ibu Pekalongan, 2021)
The Covid-19 pandemic gave birth to a new civilization era where people were asked to adapt to this pandemic condition. This also applies to maternal and child health services, especially antenatal care. The highest cause of death in Indonesia in 2019 is due to bleeding, which can be influenced by low hemoglobin levels or what is commonly known as anemia. The purpose of this study was to analyze the relationship between first trimester visits and anemia screening in pregnant women. The research method used was cross sectional, using google form media to fill out questionnaires and screen shots of the MCH book. The statistical test in this study used Pearson. The results showed that there was no relationship between the first trimester visit and anemia screening, which was obtained by the Pearson statistical test value sig = 0.189> 0.05, which means that there was no relationship between the first trimester visit and the examination of hemoglobin levels in pregnant women. The conclusion that can be drawn is that even though we are now entering a new civilization era where there are several regions that implement Large-Scale Social Restrictions and which in Maternal and Child Health services, especially pregnancy examinations, can still be implemented, government policies in the new civilization era during the 1st trimester visit are focused on screening of maternal health conditions for complications in pregnancy, and especially regarding referrals if there are complications in her pregnancy and management of pregnant women with Covid-19, so that this can prevent transmission of Covid-19.